Phenotypic Presentation of Children with Joint Hypermobility: Preclinical Signs - Mateus Marino Lamari; Neuseli Marino Lamari; Michael Peres de Medeiros; Gerardo Maria de Araújo Filho; Adriana Barbosa Santos; Matheus Gomes Giacomini; Vitor Roberto Pugliesi Marques; Eny Maria Goloni-Bertollo; Érika Cristina Pavarino (Children)
Introduction: Joint hypermobility (JH) is mobility beyond the normal range of motion. JH can be an isolated finding or a characteristic of a syndrome. Characteristics related to the sitting position with atypical body positions, such as sitting in splits (S), with the foot on the head (F), in W (W), in a concave shape (C), episodes of dislocations, and subluxations, suggest impacts on body mechanics since childhood, with damage to the conformation of the joints. Objectives: Identify preclinical signs of JH, in addition to Beighton Score (BS), through signs that are easily recognized early by pediatricians and family members to avoid possible joint deformities in the future. Methods: The medical records of 124 children (59.7% girls) between one and nine years old were analyzed. JH was assessed using the BS, a history of luxations/subluxations, and the concave (C), “W”, “splits” (S), and foot (F) on head sitting positions. Results: The concave sitting position was the most common, followed by W, F, and S in decreasing order. A total of 52.4% of the children had BS > 6, with a higher prevalence among girls (60.8%) compared to boys (40.0%); a difference statistically significant (p = 0.024, Fisher’s exact test). Thirty-two patients (27.4%) had luxations/subluxations with the higher scores. Conclusions: Sitting in S, F, W, and C positions are preclinical phenotypic characteristics of JH, easily identified by pediatricians and family members to prevent possible joint deformities. BS ≥ 6 is more frequently observed in all positions. The majority of the total sample has BS > 6, with a significant female gender influence. Among those with a history of occasional joint dislocations and subluxations, half of them have the highest BS scores.